The open d-shell enforces the active space in 3d metal catalysis: highly enantioselective chromium(II) pincer catalysed hydrosilylation of ketones - Schiwek, Christian; Vasilenko, Vladislav; Wadepohl, Hubert; Gade, Lutz H. (Chemical communications, 2018)
Bis(oxazolinyldimethylmethyl)pyrrol (PdmBox) stereodirecting ligands provided the key to the chromium(II)-catalysed highly enantioselective hydrosilylation of ketones. A rare square planar, chiral chromium(II) alkyl complex was found to serve as a potent precatalyst for the reduction of a broad range of aryl alkyl and dialkyl ketone derivatives. The stereoelectronic preference of the open d4 shell of chromium(II) firmly locks the molecular catalyst in a square planar geometry giving rise to two blocked quadrants of the coordination sphere. This earth-abundant base metal catalytic platform produces the corresponding chiral alcohols in excellent isolated yields with up to 98 %ee under mild reaction conditions (−40 °C to rt) and at low catalyst loadings (as low as 0.5 mol%).